Pengaruh Sikap dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Johny Urbanus Lesnussa; Montgomery Warbal (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Acceptance of the output of higher The effect of attitude and service quality on customer satisfaction at the Oasis swalayan in Ambon City is the title of this study. The purpose of this study was to identify how significantly customer satisfaction at Oasis Swalayan Ambon City is influenced by the attitude and service of sales officers. As many as 39 buyers from the Ambon Oasis swalayan became respondents in this study. Data was collected using a survey that combines observation and questions and literature study as a data collection technique. The data analysis technique in this study used multiple regression with the help of SPSS (Statistical Package For the Social Sciences) version 22 software. The research results show that: (1). Attitude variable (X1) with a value of 18.5 percent has a positive and significant impact on customer satisfaction (Y) (2). The results of the analysis show that with a value of 3.199 and a significance level of 0.002, the service quality variable (X2) has a positive effect on customer satisfaction (Y). Thus, it can be concluded that Attitudes and Service Quality have a positive and significant effect on Customer Satisfaction at Oasis Swalayans in Ambon city.